(3GdhUjI GdQGFYI hGdfUjMI GdaGFbIs - (3SjO eMeO Hf SjO GdeNJGQ GdcfJj,J (B1244 (3g` s
(3ChdgG (B:s
(3gPg GdhUjI GdQGFYI hGdfUjMI GdaGFbI jhUi HgG eQjOg GdCQV hCNGfG GdeQJVi eMeO Hf GdeNJGQ Hf eMeO GdWGdH CYeQ Hf NjQ s
(3BNQgG (B:s
(3BNQ eG ajgG eG Cecf bQGAJg hUa fYje GdLfI heG CYO ajgG ef GdcQGeI dChdjGFg s
(3HgG fXGe GdJYbjHIs
(3fSNI eJBcdI hHgG JbhH ai HYV ChQGbgG hcJHJ ai YUQ GdeDda HGdMHQ GdCMeQ hGdMHQGc ShOs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeYgO GdehQjJGfi ddHMK GdYdei (B((3JUha (B28) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs